Optimisation of an in vitro human cardiovascular model on-a-chip for toxicological assessment of nicotine delivery products - Chapman, Fiona; de Haan, Luuk; Gijzen, Linda; Strijker, Wouter; Sticken, Edgar Trelles; Pour, Sarah Jean; Wieczorek, Roman; Haberstroh, Florian; Otte, Sandra; Nahde, Thomas; Simms, Liam; Stevenson, Matthew (Frontiers in Toxicology, 2024)
Background Smoking cigarettes is a cause of serious diseases in smokers, including cardiovascular disease. Through a pathway of endothelial dysfunction, lipid infiltration, macrophage recruitment and vascular remodeling, atherosclerosis is fundamental in the development of most cardiovascular diseases. There is an increasing number of next-generation products (NGP) which provide potentially reduced harm forms of nicotine delivery to adult smokers. This study aimed to optimise an in vitro cardiovascular model to assess such products. Human Coronary Artery Endothelial Cells (HCAECs) were cultured on an OrganoPlate®2-lane chip (Mimetas BV) combined with THP-1 monocytes under flow conditions. Methods An aqueous aerosol extract from the 1R6F reference cigarette was compared with two categories of NGP, (a heated tobacco product (HTP) and an electronic nicotine delivery system (ENDS)), to assess relative effects on select atherogenic endpoints (oxidative stress, monocyte adhesion, ICAM-1 expression, and inflammatory markers). Following exposure of THP-1 monocytes with the aqueous extracts, the resulting conditioned medium was then added to the HCAEC vessels. Results 1R6F was consistently the most potent test article, eliciting observed responses at 4x lower concentrations than applied for both the HTP and ENDS. The HTP was more potent than the ENDS product across all endpoints, however, all test articles increased monocyte adhesion. ICAM-1 did not appear to be a main driver for monocyte adhesion, however, this could be due to replicate variability. Upon comparison to an extract-only control exposure, THP-1-medium pre-conditioning was an important mediator of the responses observed. Conclusion In conclusion, the data suggests that the NGP extracts, containing primary aerosol chemical constituents exhibit a marked reduction in biological activity in the early key events associated with atherogenesis when compared to a cigarette, adding to the weight of evidence for the tobacco harm reduction potential of such products.